As perspectivas onto-epistemológica e ético-antropológica da dualidade corpo/alma, no Fédon, de Platão - Araújo, Hugo Filgueiras de (2011)
This article deals with is an analysis of the body / soul in the dialogue Phaedo, Plato, from two perspectives: the onto-epistemological and ethical-anthropological. The ethical sense of the body trending fault the man to the passions (66bss), against the soul that leads to the practice of virtue (68-69) and the philosophical activity, the onto-epistemological part of the relationship that Plato establishes, for one hand, and the perception of body-sensitive (aisthesis) and, second, the soul and the acquisition of knowledge (episteme), more detail, between the body and soul with the sensitive and the intelligible forms. To say that Plato despised the body over the soul reflected in the statement that he despises the sense-perception at the expense of acquiring knowledge. Numerous commentators and several textbooks have been inspired in the Phaedo and the Republic to defend such contempt, that Plato, they say, manifested by feelings. However, this thesis has been causing a major problem in understanding all the work of Plato, as in the Theaetetus (152d) Plato identifies the body, in its sense-perceptual function, with knowledge, giving it a stake in this quest very relevant. The radical dualistic sense, this contempt for the body and the feeling attributed to Plato, which can be understood when reading the Phaedo is solved in the dialogue itself, as reminiscent of the arguments and the Theory of Forms, which connects the sensible to the intelligible.